Caractérisation Phytochimique des Graines et des Pulpes de Lagenaria siceraria (Molina) Standley Utilisées en Pharmacopée dans Sept (6) Régions du Niger - Sabiou, Sani Maazou Mahamane; Haoua, Sabo; Moutari, Souley Kallo; Rabiou, Maman Moustapha; Hassimi, Sadou; Bako, Aminatou; Ibrahim, Amoukou (European Scientific Journal, ESJ, 2019)
As part of the valorization of medicinal plants in Niger, a phytochemical study was carried out on the seeds and pulp of the species Lagenaria siceraria (Molina) Standley harvested in six (6) regions. The objective was to perform a phytochemical characterization, determine their variability by region and determine the best extraction solvent. Thus, extraction with solvents of increasing polarities and phytochemical screening were carried out, using standard methods, on the various samples. The results obtained show that water is the best solvent for extracting phytocomposites from Lagenaria siceraria seeds and pulp. Extraction efficiency varies by region and solvent. Phytochemical triage tests, carried out on seeds and pulp, revealed the presence of alkaloids, saponosides, flavonoids, tannins, heterosides and an absence of leucoanthocyans, catechols and cyanidins in seed and pulp extracts from certain regions. These results could justify the traditional use of Lagenaria siceraria in the treatment of certain diseases. Dans le cadre de la valorisation des plantes médicinales du Niger, une étude phytochimique a été réalisée sur les graines et les pulpes de l’espèce Lagenaria siceraria (Molina) Standley récoltée dans six (6) régions. L’objectif était de faire une caractérisation phytochimique, de déterminer leur variabilité selon les régions et de déterminer le meilleur solvant d’extraction. Ainsi, une extraction avec des solvants de polarités croissantes et un screening phytochimique ont été effectués, avec des méthodes standards, sur les différents échantillons. Lesrésultats obtenus montrent que l’eau est le meilleur solvant d’extraction des phytocomposés de graines et pulpes de Lagenaria siceraria. Le rendement d’extraction varie selon les régions et en fonction des solvants. Les tests de tri phytochimiques, réalisés sur les graines et pulpes, ont révélés la présence des alcaloïdes, des saponosides, des flavonoïdes, des tanins, des hétérosides et une absence des leucoanthocyanes, des catéchols et des cyanidines dans les extraits de graine et pulpe de certaines régions. Ces résultats pourraient justifiés l’utilisation traditionnelle de Lagenaria siceraria dans le traitement de certaines maladies.